Novel pyrromethene dyes with N-ethyl carbazole at the meso position: a comprehensive photophysical, lasing, photostability and TD-DFT study1. Issue 26 (14th July 2015) - Thorat, Kishor G.; Kamble, Priyadarshani; Ray, Alok K.; Sekar, Nagaiyan
<x xml:space="preserve">Abstract</x> Novel dyes with improved photostability and similar laser performances relative to that of the well known PM567 laser dye.